English For Specific Purposes: English Language Needs in Hospitality and Travel Industry - Nofrina Eka Putri; Dinovia Fannil Kher; Yati Aisya Rani; Azhar Jaafar Ramli (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2018)
This research is designed to identify English language needs in the hospitality and travel industry. The data was obtained from the General Manager of Garuda Indonesia Padang, the HRD Manager of Grand Zuri Hotel Padang, and 24 employees working in both those companies. The researchers used instruments; an interview and a questionnaire. Interviews were conducted with the two managers, while questionnaires were distributed to the employees of the companies. The interviews were transcribed and then analyzed using a descriptive approach. The questionnaires were analyzed Software SPSS for Windows release 22.0. This research reveals that, in the hospitality and travel industry, speaking (35%) and listening (33%) are the most needed of the four (4) language skills. These skills are primarily needed to greet customers (who are dominantly non-native speakers of English). In addition, the employees in the two companies are mostly required to serve customers whose English is basic. The findings of this research are expected to provide valuable information for ESP teachers and curriculum designers in organizing ESP syllabus and teaching materials